2013
DOI: 10.1074/mcp.r112.026823
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Platform for Comprehensive Glycan Sequencing

Abstract: From a series of recently published reports, an analytical platform has been proposed for a quantitative and qualitative measure of N-and O-glycosylation, complete with peptide-glycan connectivity and detailed structural understanding. As distant as this may appear, a best methods approach will appear that must move us beyond the cartoon stage of structural understanding. Thus, with this unifying goal in mind, we summarize a series of individually promising first phase protocols of sample preparation (release,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 30 publications
(39 reference statements)
0
45
0
Order By: Relevance
“…Glycomics represents a critical gap in knowledge in nutrition and clinical research, especially in an era of applied omic technologies. Elucidating the glycan structures that are covalently bound to peptides, proteins, and lipids requires merging the fields of glycomics with proteomics and lipidomics to truly elucidate molecular structure (108). Documenting structural diversity through comprehensive glycan analysis provides an important opportunity for understanding diet and health in the neonate.…”
Section: Milk Glycomics: Measuring Human Milk Glycansmentioning
confidence: 99%
“…Glycomics represents a critical gap in knowledge in nutrition and clinical research, especially in an era of applied omic technologies. Elucidating the glycan structures that are covalently bound to peptides, proteins, and lipids requires merging the fields of glycomics with proteomics and lipidomics to truly elucidate molecular structure (108). Documenting structural diversity through comprehensive glycan analysis provides an important opportunity for understanding diet and health in the neonate.…”
Section: Milk Glycomics: Measuring Human Milk Glycansmentioning
confidence: 99%
“…However, the permethylated glycans can lose reactivity on their reducing ends, consequently preventing their further use for fluorophore (UV detection), chromophore (chromatographic separation) or isobaric tag labeling (MS-based relative quantification) 31 . In a recent review, researchers suggested that the analysis of glycolipids, N-glycans and O-glycans will move in the direction of solid-phase extraction (SPE) methods for the sequential release of such modifications 32 . One such technique has been developed that immobilizes proteins through the use of protein G, or polyvinylidene fluoride (PVDF) 33 or lectin affinity columns 34 , allowing sequential analysis of N-glycans and O-glycans.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advancements in mass spectrometry have overcome the limitations inherent to earlier glycan profiling methodologies (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). Herein we employ an MS-based analytical approach utilizing nano-LC separation with high resolution TOF MS for accurate detection of compounds, enabling rapid identification and quantitation of N-glycan alterations during Caco-2 cell differentiation.…”
mentioning
confidence: 99%